Maria Milagros Barbarosa - Astete, Sheena Roxas 1985- (Quezon City College of Mass Communication, University of the Philippines Diliman, 2006)
" Maria Milagros "Barbie" Barbarosa is an eighteen year-old housemaid. Barbie is the breadwinner of her big family. She went to Manila hoping to alleviate the financial plight of her family. She has been with the Consolacion family for a year. Barbie has always strived to serve her employers the best way she can. And yet the Consolacion family does not seem to appreciate the dedication of their loyal servant. At the end of the day, Barbie realizes that she has become estranged from her own family. And never has she been considered part of the the family she serves. The demands of being a housemaid are more than just doing household chores. Housemaids are alienated from their own families as they try to belong in the families they serve. In a way they turn away from their personal lives because of the demands of their work. MARIA MILAGROS BARBAROSA shows more than the physical demands of the job, the mental and emotional strains that kasambahays or katulongs (housemaids) go through."
Vita.
Thesis (A.B. Film and Audiovisual Communication)--University of the Philippines Diliman